Impact of a family caregiver training program in Kolkata, India on post-operative health perceptions and outcomes of cardiothoracic surgical patients - Jessie Liu; Shahed S Alam; Rahul Guhabiswas; Malikah S Waajid; Somatree Chakrabarty; Rajanita Das Purkayastha; Rita Popat; Rajesh Gupta (Journal of Global Health Reports)
# Background